2016
DOI: 10.1177/1933719116630418
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prenatal Environmental Exposures on the Development of Endometriosis in Female Offspring

Abstract: Certain prenatal environmental exposures might result in the development of endometriosis in female offspring. In addition to known environmental exposures that predispose the development of endometriosis in adulthood, such as dioxin and radiation exposure (animal models), prenatal exposures are of increasing concern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 94 publications
(118 reference statements)
0
16
0
Order By: Relevance
“…They are known endocrine disrupters, with estrogenic and antiandrogenic effects including delayed time to pregnancy. 70 Exposure to environmental toxins during the prenatal period is thought to have the greatest effect on reproduction and endometriosis, 71 and elevated serum phthalates in women are associated with endometriosis. 72,73 However, our search could not locate any publications on the specific effect of environmental pollutants or other environmental factors on endometrial stem/progenitor cells.…”
Section: Environmentmentioning
confidence: 99%
“…They are known endocrine disrupters, with estrogenic and antiandrogenic effects including delayed time to pregnancy. 70 Exposure to environmental toxins during the prenatal period is thought to have the greatest effect on reproduction and endometriosis, 71 and elevated serum phthalates in women are associated with endometriosis. 72,73 However, our search could not locate any publications on the specific effect of environmental pollutants or other environmental factors on endometrial stem/progenitor cells.…”
Section: Environmentmentioning
confidence: 99%
“…Several studies have highlighted the negative effects of BPA on reproductive system [17]. Particularly, it has been shown that BPA displays a high affinity for ER, having an estrogen-mimicking behavior and consequently stimulating estrogen function [11][12][13]; therefore, BPA has been hypothesized to be involved in several diseases of female reproductive system [3,[18][19][20][21][22], due to its property to stimulate ER-dependent gene expression involved in the pathophysiology of female reproductive system [23][24][25][26]. Moreover, BPA is also able to inhibit androgen function by binding AR [27].…”
Section: Introductionmentioning
confidence: 99%
“…PCBs may inhibit the activity of human estrogen sulfotransferase, an estrogen-degrading enzyme (Kester et al 2000), thereby increasing the secretion of estrogen and the risk of hormone-dependent diseases. Accumulating evidence had suggested that higher PCBs exposure may increase the risk of endometriosis (Hu et al 2018;Martinez-Zamora et al 2015;Porpora et al 2006;Wei et al 2016). A reduced responsiveness to progesterone and overexpression of matrix metalloproteinases may be a key element of endometrial dysfunction associated with endometriosis (Osteen et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Intrauterine exposure to an adverse environment will not only affect fetal development and lead to unfavorable pregnancy outcomes, but it will also have long-term impacts on disease susceptibility into late adulthood (Barker 1997;Godfrey and Barker 2001), including endometriosis (Wei et al 2016).…”
Section: Introductionmentioning
confidence: 99%